2010
DOI: 10.4103/0972-124x.75911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of periodontal status among patients with cleft lip, cleft palate, and cleft lip along with a cleft in palate and alveolus

Abstract: Background and Objectives:A healthy periodontium is an important prerequisite for unhindered dentition and long-term oral health. In cleft subjects, especially in those with cleft lip, alveolus and palate (CLAP), maintenance of oral hygiene is a difficult task for the patients because of the patent oro-nasal communication. Crowding of teeth in cleft patients is a common finding, especially in those with CLAP and those with cleft palate (CP). In the case of multiple tooth-malpositions, transverse deficiency, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 17 publications
0
30
0
9
Order By: Relevance
“…The periodontal status was recorded by using a CPITN Index [19]. The present study shows that the healthy periodontium was found to be 38.5% in Cleft Lip group, whereas in a study by Vinita Boloor et al, [6] reported that the healthy periodontium was 28.8%. This difference can be attributed to the regular dental check-up and good oral hygiene practices for the children by the parents in the present study.…”
Section: Resultsmentioning
confidence: 41%
See 4 more Smart Citations
“…The periodontal status was recorded by using a CPITN Index [19]. The present study shows that the healthy periodontium was found to be 38.5% in Cleft Lip group, whereas in a study by Vinita Boloor et al, [6] reported that the healthy periodontium was 28.8%. This difference can be attributed to the regular dental check-up and good oral hygiene practices for the children by the parents in the present study.…”
Section: Resultsmentioning
confidence: 41%
“…But the presence of periodontitis is seen more in subjects with cleft lip alveolus and palate (CLAP) also more destruction is seen in adjacent to the teeth [6].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations